Online Political Communication: How to Use the Web to Build Consensus and Boost Participation - Giansante, Gianluca (Springer, 2015)
This book provides research findings and practical information on online communication strategies in politics. Based on communication research and real-world political-campaign experience, the author examines how to use the Web and social media to create public visibility, build trust and consensus and boost political participation. It offers a useful guide for practitioners working in the political arena, as well as for those managing communication projects in institutions or companies